Pengaruh beban kerja terhadap burnout karyawan pada PT PLN (persero) dengan dukungan sosial sebagai variabel pemediasi - Elsa Juhnisa; Yuki Fitria (Universitas Negeri Padang, 2020)
This study aims to analyze: (1) The influence of workload influences burnout on the employees of PT PLN (Persero) Unit Induk Wilayah Riau dan Kepulauan Riau. (2) The influence of the workload influences social support on the employees of PT. PLN (persero) Unit Induk Wilayah Riau dan Kepulauan Riau. (3) The effect of social support influences burnout on the employees of PT. PLN (Pesero) Unit Induk Wilayah Riau dan Kepulauan Riau. (4) The influence of workload on social support mediated by social support on the employees of PT. PLN (Persero) Unit Induk Wilayah Riau dan Kepulauan Riau. This type of research is describtive causative research. The population in this study employees of PT. PLN (Persero) Unit Induk Wilayah Riau and Kepulauan Riau, totaling 125 people. In this study the number of samples determined using Slovin collected samples obtained by 95 people taken using proportional clustered simple random sampling is the sample selected in each class or group that matches the proportion and added by each family member to the same sample. This research uses PLS (Partial Least Square) data analysis method using SmartPLS sotfware which is a variance-based structural equation analysis (SEM) that can simultaneously conduct measurement model testing as well as structural model testing. Regarding the proposed causal model, the data confirm the relationship established in the hypothesis. Therefore, it can be stated that (1) Workload has a significant positive effect on the burnout of the employees of PT. PLN (Persero) Unit Induk Wilayah Riau dan Kepulauan Riau. (2) The workload has a significant negative effect on social support on the employees of PT. PLN (Persero) Unit Induk Wilayah Riau dan Kepulauan Riau. (3) Social support has a significant negative effect to the burnout of the employees of PT. PLN (Persero) Unit Induk Wilayah Riau dan Kepulauan Riau. (4) Social support has significantly mediated the relationship between workload on burnout in PT. PLN (Persero) Unit Induk Wilayah Riau dan Kepulauan Riau. This analysis highlights the negative influence of workload on burn out and the role of social support as mediating the relationship of workload with burnout. This is clearly seen in this connection from an empirical point of view Keywords: Burnout, social support, workload.